W12 Twitter for clinical educators. (5th November 2017) - Gopal, A; Gay, C; Abel, A
Abstract : Background: Student ASPiH (sASPiH) is the special interest group for students within the Association for Simulated Practice in Healthcare (ASPiH). Social media is currently one of the major technology-enhanced-learning (TEL) areas of interest for clinical educators, however the investment of time and risk-benefit profile often mean that it is under-utilised as a tool for engagement and education. Twitter in particular is often considered the most professional of social media tools, with citation of tweets now accepted in most major referencing systems. Aims: To aid educators to gain insight into the role twitter can play for them and their institute; raising awareness, building brand recognition, encouraging networking and collaboration in addition to the use of twitter to directly provide clinical education. Learning objectives: By the end of the session, attendees should be able to: Demonstrate insight into the role that twitter can play in engagement as well as usage as a tool for educating, both scheduled and opportunistic. Understand the limitations and risks involved with professional usage, and ensuring compliance with their host organisation's policy. Demonstrate a basic understanding of Ížtweet etiquetteÍŸ and ways to increase followership of the intended groups of interest. Educational methods: The first part will be a powerpoint and interactive demonstration showcasing tools such as tweetdeck and twitter analytics to enhance usage of the platform, including how it can be used to teach.The second part will discuss the value and risks of twitter to educators, using powerpoint and flipcharts to encourage discussion of experiences and insight. Finally, we will encourage attendees to pick a particular focus of interest at the conference and draft 2–3 tweets for use over the coming day, with facilitators on hand to explain Ížtweet etiquetteÍŸ. Target audience: any delegate interested in using twitter for professional engagement or education.Maximum of 20 participants please. Room layout: Cabaret style. AV preferences: A projector with HDMI input. We will supply a chrome OS laptop and chrome cast to show live demonstrations and highlight examples of work within the workshop using the HDMI connection.